The Premises of Public-Private Partnership (PPP) - A Comparative Analysis Based on Selected Municipalities in Małopolska - Węgrzyn, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The aim of this paper is to determine the motives to implement public-private partnership (PPP) in municipalities. It was assumed that the implementation of such projects is determined by characteristics that can be aggregated into three areas: the availability of infrastructure, the size of the financial resources at the disposal of municipalities, and the ability to finance an investment project without exceeding the limits of liability. A quantitative study of these relations was done using taxonomic analysis. The study failed to clearly resolve the impact of having an infrastructure gap on PPP decisions. The results have confirmed, however, that municipalities are suffering from rising public debt, which threatens the investment process. Research shows that PPP is perceived by the communities under consideration as a remedy to the problems associated with obtaining investment financing.